Difficulties of nurses in basic care for people living with HIV/AIDS (Research, Society and Development, 2021)
The human immunodeficiency virus (HIV) is a sexually transmitted infection (STI) that mainly affects the immune system, affecting several people in the world, thus constituting a public health problem. In primary care, there is the first contact between nurse and patient, promoting, then, a service with clear guidelines on the HIV / AIDS virus. Objective: to analyze through a literature review the main difficulties in nursing care for PLHIV in primary care. Methodology: this is an integrative literature review of an explanatory type, of a qualitative character, carried out between August 2020 and May 2021, presenting in the databases of the Virtual Health Library (VHL) platform indexed in the databases. data, Scientific Eletronic Library Online (SCIELO), Latin American and Caribbean Literature in Health Sciences (LILACS) Medical Literature Analysis and Retrieval System Online (MEDLINE). Qualitative and quantitative studies were published, published in the last 10 years in Brazil, with complete texts and available in full and excluded without relevance to the theme and repeated in the search bases. After detailed reading, 15 articles were selected for the preparation of the study. Results: the study obtained data that describe the difficulties in nursing care for PLHIV, carried out in different regions of Brazil (North, Northeast, South and Southeast). Conclusion: Therefore, the articles show the failures of the public system in relation to the primary care in which they are linked to the logistics of inputs and materials, limiting assistance and impairing access to a quality service.